2012
DOI: 10.4049/jimmunol.1102691
|View full text |Cite
|
Sign up to set email alerts
|

The IL-2 Diphtheria Toxin Fusion Protein Denileukin Diftitox Modulates the Onset of Diabetes in Female Nonobese Diabetic Animals in a Time-Dependent Manner and Breaks Tolerance in Male Nonobese Diabetic Animals

Abstract: Denileukin diftitox, also known as DAB389IL-2 or Ontak, is a fusion protein toxin consisting of the full-length sequence of the IL-2 protein and as toxophore the truncated diphtheria toxin. As a consequence, it delivers the toxic agent to CD25-bearing cells, whereby CD25 represents the high-affinity α-subunit of the IL-2 receptor. Initially it was developed for the treatment of patients with cutaneous T cell lymphoma. Meanwhile, denileukin diftitox is also used as an adjuvant in other tumor therapies and neopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Injection of Ontak ® into mice has been observed to deplete T regs and enhance T-cell immunity 7 . However, in the non-obese diabetic (NOD) mouse model of human type-1 diabetes, we reported that Ontak ® either promoted disease or had no effect, depending on the time point of application 8 . Several clinical studies (cited in ref.…”
mentioning
confidence: 98%
“…Injection of Ontak ® into mice has been observed to deplete T regs and enhance T-cell immunity 7 . However, in the non-obese diabetic (NOD) mouse model of human type-1 diabetes, we reported that Ontak ® either promoted disease or had no effect, depending on the time point of application 8 . Several clinical studies (cited in ref.…”
mentioning
confidence: 98%